Investigation of heat transfer between 22MnB5 and KDAHP1 hot work tool steel. Issue 12 (13th August 2021) - Tang, Ziming; Gu, Zhengwei; Wang, Gang; Han, Yuting; Yi, Lingling; Xu, Meng; Li, Yusheng; Hou, Wenliang; Yu, Ge
Abstract : The IHTC (Interfacial-Heat-Transfer-Coefficient) between 22MnB5 and KDAHP1 hot work tool steel during the hot stamping process is an important thermal parameter to reflect the heat transfer efficiency. The instantaneous heat transfer law for 22MnB5 blank is based on the cylindrical-die model, and the experiment is contained different contact pressure and gap conditions. The average IHTC value is calculated by the heat balance method (HBM) and finite element optimisation method (FEOM). There is a power function relationship between the average IHTC and both the contact pressure and the one-side gap. From the results of the one-side and bilateral gap condition, 0.2 mm can be considered as the 'critical gap' where the heat exchange between the blank and dies starts or ends.